Issues in predicting the demand for a new technological product - Klaus K. Brockhoff; Vithala R. Rao (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1991)
This paper focuses on various issues that need to be considered when an analyst wishes to predict the demand for a new technological product. The interplay of the strategic behavior of the firm, notably with regard to preannouncing the future availability of the new product and the behavior of channel members and prospective customers is highlighted in this paper. Prospective customers' choice behavior is governed by such factors as credibility of the firm's preannouncement and expectations on the availability of the new product while a channel member's decision to accept the new product depends upon the expected sales and a demonstration of the product's acceptance by other channel members. These issues lead logically to the interdependence between the product positioning and the preannouncement decisions potential of the firm. The paper concludes with a discussion of the data requirements for implementing the approach suggested by the model and implications for product development process and competitive behavior.
Keywords: 650; Innovation; Theorie